Densities and Refractive Indices of Potassium Salt Solutions in Binary Ethanol+Water Mixture of Different Compositions. (8th November 2012) - Deosarkar, S. D.; Pandhare, V. V.; Kattekar, P. S.
Abstract : Densities and refractive indices of solutions of different concentrations of potassium salts, namely, KCl, KBr, and KI in 10%, 20%, 40%, and 60% (v/v) ethanol-water mixture were measured at 303.15 K. Specific refractions (R D ) and molar refractions (R M ) have been estimated from measured refractive indices and densities of solutions and interpreted in terms of interactions in salt solutions. Refractive indices increased with an increase in percentage of ethanol as well as with concentrations of potassium salts for given composition of binary solvent mixture.